Zno/Ag Nanocomposite Thin Films: A Promising Approach for Dye Degradation - Gilliot, Mickaël; Lazar, Florica; Hadjadj, Aomar; Khiari, Mouna; Lejeune, Michaël (Aspects in Mining & Mineral Science, 2021)
Forecasts for the global textile dyes market would indicate a growth from some US $7 billion in 2019 to more than US $13 billion in 2027, despite stringent environmental regulations...